REFLEKSI FILOSOFIS TERHADAP KONSEP SEJARAH FRANCIS FUKUYAMADARI BUKU THE END OF HISTORY AND THE LAST MAN - Wawaysadhya Wawaysadhya (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2019)
This paper is analyzing the thought of Francis Fukuyama based on his book “The End of History and The Last Man”, for his contribution in philosophy of history, and the effected of the historical motion that occurred in Indonesia. Fukuyama explained that liberal democracy will have significant impact on the world social and technological development, which transforms human life into technology dependence. Now, Humans are "headless" and living his life with desire for technology.This article discussedby the point of view of historical philosophy to analize type of history that forms the basis of Francis Fukuyama's mind. The result is that history is now an open process with various possibilities in the future, where humans are not a means to embody ideas, but history begins and ends with people who have the freedom to regulate their future. History is a human partnership to realize freedom at certain times and places.